The power of the textbook: A framework for analysing the construction of pedagogic identities and pedagogic knowledge in textbooks = Siła podręcznika: ramy analizy konstrukcji tożsamości pedagogicznych i wiedzy pedagogicznej w podręcznikach - Svendsen, Jesper Tinggaard (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The main premise of this paper is that the textbook should be understood to be at one and the same time a particularly powerful document to establish and maintain dominant discourses and a seismograph for the reading such discourses. In this way, the textbook is not just at tool to enhance learning but also a place where pedagogic identities and pedagogic knowledge is constructed.
Keywords: tożsamość; tożsamość aktywna; tożsamość pasywna; tożsamość deliberatywna; memetyka; identyfikacja; samoidentyfikacja; język; językoznawstwo; językoznawstwo polskie